2020
DOI: 10.1155/2020/6786875
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Diagnostic Value of Exosomal Long Noncoding RNAs in Solid Tumors: A Meta‐Analysis and Systematic Review

Abstract: Background. Exosomes are defined as small membranous vesicles. After RNA content was discovered in exosomes, they emerged as a novel approach for the treatment and diagnosis of cancer. Long noncoding RNAs (lncRNA), a kind of specific RNA transcript, have been reported to function as tumor growth, metastasis, invasion, and prognosis by regulating the tumor microenvironment in exosomes. This study aims at exploring the potential diagnostic of exosomal lncRNA in solid tumors. Methods. A meta-analysis conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Silencing the expression of circ_0044516 in PCa cells corroborated with a reduction in growth and metastasis of cancer cells. Similar roles of non-coding RNAs such as exosomal lncRNAs have been described in PCa [ 166 ]. Exosomal lncRNA H19 is known to be upregulated in serum in cases of bladder cancer, thus, having a potential role as a prominent diagnostic marker [ 167 ].…”
Section: Applications Of Tumor Derived Extracellular Vesicles From Li...supporting
confidence: 55%
“…Silencing the expression of circ_0044516 in PCa cells corroborated with a reduction in growth and metastasis of cancer cells. Similar roles of non-coding RNAs such as exosomal lncRNAs have been described in PCa [ 166 ]. Exosomal lncRNA H19 is known to be upregulated in serum in cases of bladder cancer, thus, having a potential role as a prominent diagnostic marker [ 167 ].…”
Section: Applications Of Tumor Derived Extracellular Vesicles From Li...supporting
confidence: 55%
“…Higher expression levels of exosomal lncRNA-H19 compared to parental cells have been reported in DOX resistance [ 380 ]. A recent meta-analysis has confirmed that lncRNAs in SEVs could be a promising bioindicator for the diagnosis and prognosis of solid tumors [ 483 ].…”
Section: Exosomes As Relevant Breast Cancer Biological Markersmentioning
confidence: 99%
“…Elevated concentrations of specific circRNAs in exosomes correlate with the presence of ovarian, prostate, and lung cancers (Wang Y. et al, 2019). In addition to miRNAs and circRNAs, other non-coding RNAs, such as lncRNAs in exosomes also play an important role in the diagnosis and monitoring of tumors (Wu et al, 2020). Recent studies have suggested that exosomal lncRNA-GC1 can be used as noninvasive biomarkers in the early detection of gastric cancer and in monitoring its progression (Guo et al, 2020).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%